A Low-Cost Data Acquisition For CMOS-Based Optical Tomography System - Rahim, Norain; Ab Aziz, Ab Wafi; Mustaffa, Izadora; Wan Hassan, Wan Haszerila; Che Aziz, Siti Asma (Penerbit Universiti, UTeM, 2017)
This paper presents the development of a portable, effective and economical Data Acquisition (DAQ) for optical tomography system. DAQ is a core unit that is essential for acquiring an accurate yield for data sampling in Tomography System. However, there are extremely limited quantities of equipment in market that can accurately implemented as DAQ for the optical tomography system. This project offers a microprocessor-based data acquisition system which able to demonstrate the output pixel of CMOS image sensor in GUI application. The project drives the control unit (LPC2103) to perform data sampling for CMOS image sensor and allocate 128x64 of data pixels into a visualized image inside the GUI application.